2015
DOI: 10.1002/jhm.2260
|View full text |Cite
|
Sign up to set email alerts
|

Improving appropriateness of acid-suppressive medication use via computerized clinical decision support

Abstract: As part of the Choosing Wisely Campaign, the Society of Hospital Medicine identified reducing inappropriate use of acid-suppressive medication for stress ulcer prophylaxis as one of 5 key opportunities to improve the value of care for hospitalized patients. We designed a computerized clinical decision support intervention to reduce use of acid-suppressive medication for stress ulcer prophylaxis in hospitalized patients outside of the intensive care unit at an academic medical center. Using quasi-experimental i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 12 publications
0
23
0
Order By: Relevance
“…Second, the lack of a documented indication does not exclude the possibility that there was an undocumented evidenced‐based indication. Prompting clinicians to document an indication for long‐term prescriptions can mitigate this clinical uncertainty while simultaneously improving documentation and the quality of care …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, the lack of a documented indication does not exclude the possibility that there was an undocumented evidenced‐based indication. Prompting clinicians to document an indication for long‐term prescriptions can mitigate this clinical uncertainty while simultaneously improving documentation and the quality of care …”
Section: Discussionmentioning
confidence: 99%
“…Prompting clinicians to document an indication for long-term prescriptions can mitigate this clinical uncertainty while simultaneously improving documentation and the quality of care. 12,24 CONCLUSIONS Older adults are receiving PPI prescriptions at an alarmingly high rate, often against guidelines. This study suggests that potentially minor changes in EHR-based stopping rules and/or targeted physician profiling could have a substantial impact on reducing low-value prescribing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results demonstrated a significant but small reduction in the caesarean delivery rate. Herzig et al (2015) described a quasi-experimental study using interrupted time series to improve the appropriateness of acid-suppressive medication (Herzig et al, 2015). This type of medication is not indicated but is commonly used for stress ulcer prophylaxis in patients outside intensive care.…”
Section: Implementation Vs De-implementationmentioning
confidence: 99%
“…In the study by Herzig et al 4 investigators took on the challenge of implementing stress ulcer prophylaxis guidelines developed by the Society of Hospital Medicine. The investigators first demonstrated that targeted electronic prompts captured patients' indications for acid suppressive therapy, and could be used to prohibit prescribers from ordering acid suppressive therapy among patients outside the intensive care unit (ICU) setting.…”
mentioning
confidence: 99%